External Validity of Randomized Controlled Trials on Alzheimer’s Disease: The Biases of Frailty and Biological Aging - Canevelli, Marco; Trebbastoni, Alessandro; Quarata, Federica; D’Antonio, Fabrizia; Cesari, Matteo; de Lena, Carlo; Bruno, Giuseppe (Frontiers in Neurology, 2017)
To date, the external validity of randomized controlled trials (RCTs) on Alzheimer’s disease (AD) has been assessed only considering monodimensional variables. Nevertheless, looking at isolated and single characteristics cannot guarantee a sufficient level of appreciation of the AD patients’ complexity. The only way to understand whether the two worlds (i.e., research and clinics) deal with the same type of patients is to adopt multidimensional approaches more holistically reflecting the biological age of the individual. In the present study, we compared measures of frailty/biological aging (assessed by a Frailty Index, FI) of a sample of patients with AD resulted eligible and subsequently included in phase III RCTs compared to patients referring to the same clinical service, but not considered for inclusion. The “RCT sample” and the “real world sample” were found to be statistically similar for all the considered sociodemographic and clinical variables. Nevertheless, the “real world sample” was found to be significantly frailer compared to the “RCT sample”, as indicated by higher FI scores (0.28 [SD 0.1] vs. 0.17 [SD 0.1]; p<0.001, respectively). Moreover, when assessing the relationship between FI and age, we found that the correlation was almost null in the “RCT sample” (Spearman’s r=0.01; p=0.98), while it was statistically significant in the “real world sample” (r=0.49; p=0.02). The application of too rigid designs may result in the poor representativeness of RCT samples. It may even imply the study of a condition biologically different from that observed in the “real world”. The adoption of multidimensional measures capable to capture the individual’s biological age may facilitate evaluating the external validity of clinical studies, implicitly improving the interpretation of the results and their translation in the clinical arena.